Global Economical Justice in the International System of States - Cortés Rodas, Francisco (Estudios de Filosofía, 2009)
This article discusses some of the proposals that modern and contemporary discussions offer on the normative methods for a New International Order. It treats of the possibility of demanding, as a matter of justice, the transformation of the relations of power in the International economical and political orders, between the richest societies and the poorer ones. Four different models of Internal and Interstate State Order are exposed and criticized. First) The realist model of the Absolutist State which establishes peace internally and externally through dissuasion, and which denies that a criteria of justice can be formulated to de ne the relations between states. Second) The Kantian model of State of Law. Third) The Social State of Rawls with two differentiated models of the contract to de ne the relations in the interior and the exterior and Fourth) the Cosmopolitan Project. Finally, the liberal Project of Justice is criticized because it reduces the problem of the Re-Ordering of the International Order to distributive justice and does not question the structures of the actual Global Economic System.